Diplomacia científica e governança pública nas instituições de ensino superior - Taniguti, Barbara Sayuri Poffo (2025)
Science diplomacy has been emerging as an essential element of public governance, particularly by enabling the formulation of evidence-based public policies and promoting international cooperation through the increased global representations of countries. Higher education institutions (HEIs) play a fundamental role in this context, fostering the internationalization of knowledge through various mechanisms, such as academic mobility and participation in transnational scientific networks. Within this framework, this study aims to analyze the relationship between science diplomacy and public governance by examining the role of HEIs in internalization and scientific cooperation, using the Bragança Polytechnic University (IPB) in Portugal and the Federal Technological University of Paraná (UTFPR) in Brazil as paradigm institutions. These institutions were chosen due to their strong emphasis on internalization, wellestablished partnerships in academic mobility and joint scientific research networks, and direct connection to the researcher though a dual-degree master’s program. Methodologically, a qualitative approach was chosen, primarily employing bibliographic and documentary research, as well as semi-structured interviews with IPB and UTFPR managers. The results highlight that HEIs play a crucial role in formulating evidence-based public policies and promoting sustainable development which confirms that academic internationalization strengthens science diplomacy and directly impacts public governance, making it more effective and efficient. Furthermore, the study proposes a science diplomacy network model, emphasizing its potential to strengthen ties between Brazil and Portugal and to promote science diplomacy as a strategic tool for sustainable development and governance at both local and global levels. Thus, this research reaffirms the essential role of HEIs in formulating evidencebased public policies, positioning science diplomacy as a pillar of contemporary public governance.